Swimming Athletes Guidance and Training at Arhesa Swimming Club Bandung - Arhesa, Sandra; Gaffar, Vanessa; Ma'mun, Amung (Indonesian Journal of Sport Management, 2024)
This research aims to describe the coaching and training patterns of swimming athletes at Arhesa Swimming Club Bandung. The research method used is qualitative research using descriptive methods. The subjects of this research include management and coaches. Observation, interviews, and document analysis were carried out during data collection. The results of this research are that achievement development has been carried out in a planned and programmed manner, the organizational situation could be better, facilities and infrastructure still need to be improved, and the achievements achieved by athletes so far still need to be exemplary. The study shows that the condition of the club organization could be running better, and the management system needs to be reorganized regularly. The organization's work program needs to be structured due to limited funds and lack of support for facilities and infrastructure. The achievement development program is carried out systematically, regularly, continuously, planned, and programmed with maximum reference to technical training. The existing coaches have good quality, but the number needs to be commensurate with the athletes. The number of training facilities and infrastructure still needs to be improved to meet standards. However, the achievements obtained have been encouraging at the local and regional levels. The Arhesa Club is recommended to strengthen and develop organizational systems and coaching patterns to achieve the highest achievements. Looking for alternative funds or sponsors to add training equipment to increase athletes' training activity is necessary.